GERAKAN ISLAM KEBANGSAAN MBAH MUQAYYIM; KAJIAN HISTORIS RELASI KERATON KANOMAN DAN PESANTREN BUNTET CIREBON - Yoyon Yoyon (Mozaic : Islam Nusantara, 2018)
The article talks about a relationship system between keraton and pesantren in Cirebon in the framework of the history of the 18th M century. It Refers to discussion tendency about pesantren and its authority. Both two institutions are interpreted in a separate manner. Whereas there is evidence that this relationship between pesantren and keraton as an institution power in Java has a close connection. This study is based on an argument that keraton and pesantren have a close relationship with a side lineage or in building Cirebon Islamic character. Except use a historical approach, this research also uses a multidimensional approach through many knowledge discipline approaches, such as Anthropology, Sociology, and Cultures. This article is not only revealing the historical element of keraton relationship but also discusses Islamic nationality movement by a mufti figure, Mbah Muqayyim. An against religion movement’s figure to colonialist which basically, is spirit protection the religion and nationality. The result can be concluded that keraton and pesantren relationship system in Cirebon is made through kinship, scientific transmission and tradition preservation concept Where Mbah Muqayyimas an important figure who contributes to saving the keraton’s religious tradition which is threatened by colonialist dominance in surroundings Keraton Kanoman